Gambaran karakteristik gagal jantung pada anak di RSUP Prof. Dr. R. D. Kandou Manado - Anthonius, Agnes A.; Kaunang, Erling D.; Runtunuwu, Ari L. (e-CliniC, 2016)
Abstract: Heart failure is the inability of the heart to pump adequate blood that fulfils the metabolic demands of the body, including growth. In Indonesia, it is still difficult to find the prevalence and incidence of heart failure in children. This study was aimed to determine the characteristic features of heart failure in children at Prof. Dr. R. D. Kandou Hospital Manado. This was a retrospective descriptive study with a cross-sectional design. Data were obtained from the medical records of pediatric patients with heart failure within the period of January 2013 to August 2016 in the Child Health Department at Prof. Dr. R. D. Kandou Hospital. The results showed that there were 69 children with heart failure; the most common were females and age 12-18 years. The most common signs and symptoms were shortness of breath, fever, and cough. Heart murmurs and gallop were frequently found. Hepatomegaly, splenomegaly, ascites and edema of the legs were not commonly found. The electrocardiogram results were mostly sinus rhythm. The echocardiography results were mostly mitral regurgitation. The most common comorbid disease was rheumatic heart disease. Conclusion: At Prof. Dr. R. D. Kandou Hospital, heart failure in children was mostly found among females and age of 12-18 years. Most of the children showed shortness of breath, fever, and cough.Keywords: heart failure, child, characteristic featuresÂ Abstrak: Gagal jantung merupakan ketidakmampuan jantung sebagai pompa darah untuk memenuhi secara adekuat kebutuhan metabolisme tubuh termasuk pertumbuhan. Di Indonesia sendiri masih sulit menemukan data prevalensi dan insiden gagal jantung pada anak. Penelitian ini bertujuan mengetahui gambaran karakteristik gagal jantung pada anak di RSUP Prof. Dr. R. D. Kandou Manado. Jenis penelitian ialah deksriptif retrospektif dengan desain potong lintang. Data penelitian diambil dari rekam medik pasien anak dengan gagal jantung periode Januari 2013 sampai Agustus 2016 di Bagian Ilmu Kesehatan Anak RSUP Prof. Dr. R. D. Kandou Manado. Hasil penelitian mendapatkan 69 anak, terbanyak pada usia 12-18 tahun dan jenis kelamin perempuan. Tanda dan gejala terbanyak ialah sesak napas, demam, dan batuk. Bising jantung dan galop banyak ditemukan. Hepatomegali, splenomegali, ascites dan edema tungkai tidak banyak ditemukan. Hasil elektrokardiogram terbanyak ditemukan ialah irama sinus. Hasil ekokardiografi terbanyak ditemukan ialah regurgitasi mitral. Penyakit penyerta terbanyak ialah penyakit jantung rematik. Simpulan: Gagal jantung anak di RSUP Prof. Dr. R. D. Kandou Manado terbanyak pada usia 12-18 tahun, jenis kelamin perempuan, dengan gejala klinik sesak napas, demam, dan batuk. Kata kunci: gagal jantung, anak, gambaran karakteristik